UTILIZATION OF PALM SHELLS FROM ENVIRONMENTAL LEGAL PERSPECTIVE TO IMPROVE THE ECONOMY - Kurniadi; Syafrinaldi; Thamrin S (International Conference On Law And Social Sciences, 2024)
Environmental law and the Sustainable Development Goals (SDGs) are very important and related to each other, especially in Indonesia. For achieving the SDGs, law environment very importance, and role law national very useful, so that it happens continuity source Power nature, esp environment in Indonesia. Regulation Indonesian national laws, such as the Constitution Environment 2009 and its derivative regulations, offer a framework clear work to protect source power, nature, and the environment. Regulations This naturally supports the initiative of government to reach a sustainable system in the SDG context. So that sustainability life walk period long. Aligned with the draft, it is connected with industry. Palm oil, with lots of it growing and developing in Indonesia, already should be an be an industry. This is tied to the concept of the of the SDGs: to reduce waste as well as get used to thinking innovatively, so you can do it to increase economy, then need to utilize shell palm. So, identify the problem. How utilization of shell palm oil in Indonesia, views from a glass law environment To increase the economy. The research method used, namely normative law and study library, used approach concepts and regulations and legislation. The result found that the utilization shell palm oil in Indonesia is viewed from a glass law environment. To increase the economy, namely something innovative, the Sustainable Development Goals (SDGs) really are tightly tied to the management of shell palm oil, especially in Indonesia. SDGs can be achieved through the utilization or management of shell palm in a sustainable manner. Shell management sustainable palm oil will be able to muffle emissions of carbon with the use energy as a supporting action for climate change, which becomes one of the one of the SDGs goals. Moreover possible can increase field decent work, improvement income, and increase well-being public local.